2018
DOI: 10.1136/sextrans-2017-053277
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of HIV and TB/HIV coinfection in a middle-income country: a costing analysis alongside a pragmatic clinical trial in Brazil

Abstract: RBR-22t943, Results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…It was found that the population characteristics of TB/HIV infection were different in different demographic variables. In terms of age, patients aged 20-40 had the highest HIV infection rate, followed by patients aged over 40, and patients aged younger than 20 had the lowest HIV infection rate, which was similar to the study results of Teixeira et al (2018) (24). The reason may be that people over 40 were sexually active and had higher rates of risky sex.…”
Section: Gene Mutation Characteristics Of Multidrugresistant Mtbsupporting
confidence: 89%
“…It was found that the population characteristics of TB/HIV infection were different in different demographic variables. In terms of age, patients aged 20-40 had the highest HIV infection rate, followed by patients aged over 40, and patients aged younger than 20 had the lowest HIV infection rate, which was similar to the study results of Teixeira et al (2018) (24). The reason may be that people over 40 were sexually active and had higher rates of risky sex.…”
Section: Gene Mutation Characteristics Of Multidrugresistant Mtbsupporting
confidence: 89%
“…Another limitation was that our dataset did not include socioeconomic status measures such as income, education, and assets, which are important predictors of seeking and sustaining medical treatments, especially in resource-limited countries. For instance, Teixeira de Siqueira-Filha and colleagues concluded that patients with TB/HIV coinfection had a higher economic burden than patients with HIV only and also that death resulting from TB/HIV coinfection can cost almost three times more than a death attributable to AIDS [ 34 ]. Thus, extremely poor patients may decide to purchase food instead of medication.…”
Section: Discussionmentioning
confidence: 99%
“…The fixed or random-effect model was applied based on the heterogeneity test. If I 2 >50% or p<0.10, we selected the random-effects model; otherwise, we applied the fixed-effects model. Meta-regression analysis was used to explore the causes of heterogeneity.…”
Section: Methodsmentioning
confidence: 99%
“…Globally, an estimated 10.0 million people fell ill with tuberculosis in 2018, a number that has been relatively stable in recent years. 1 Coinfection with tuberculosis and AIDS, 2 tuberculosis and diabetes, 3 liver damage caused by antituberculosis drugs 4 and ambient air pollution 5 are all huge obstacles to achieve the 'End Tuberculosis Goal'. According to the WHO, the number of persons with both incident and prevalent tuberculosis remains the highest in the South-East Asian and African regions.…”
Section: Introductionmentioning
confidence: 99%